In Vitro and In Silico Studies on the Anticancer and Antimicrobial Activity of Cu(II), Ni(II) and Co(II) Complexes with Bis (Pyrazolyl) Borate Derivative Ligand - Monireh Ghorbanpour; Behzad Soltani; Ommoleila Molavi; Elnaz Mehdizadeh Aghdam (Tabriz University of Medical Sciences, 2022)
Background: The development of the pyrazole-based complexes is greatly enhanced due to the identification of their structure as medicinal application. Keeping in view therapeutic and biological activities of pyrazoles based compounds and the potential of transition metals in the antimicrobial application area, we find it vital to join the chemistry of both moieties in designing and developing biometal compounds which could aggressively work against various bacterial species and cancer cells. In this work, we report the synthesis and characterization of copper (II), nickel (II) and cobalt (II) complexes of dihydrobis(pyrazolyl)borate ligands. Also, antibacterial activities, MTT assay and molecular docking of these compounds were investigated. Methods: A bidentate N-donor pyrazole-based ligand abbreviated as K[H2B(PzMe2)2] and corresponding complexes with Cu(II), Ni(II) and Co(II) were synthesized and characterized. The anticancer activities of the synthesized compounds were studied against the (MDA-MB-231) cell lines. The antibacterial investigations of the synthesized compounds against the gram-positive (B. subtilis) and the gram-negative (S. enterica) bacteria were performed. In addition, molecular docking of the synthesized compounds with YmaH (PDB ID: 3HSB) protein, ecKAS III (PDB ID:1HNJ) protein and DNA dodecamer (PDB ID: 1BNA) as the possible targets was studied. Results: The result showed among the investigated compounds, complex [Cu(H2B(PzMe2)2)2] indicated the highest cytotoxicity and bacterial inhibition. Conclusion: In summary, we have synthesized a type of N- donor pyrazole-based ligand and corresponding metal complexes. In silico molecular docking along with the experimental MTT assay and antibacterial studies, indicated the metal complexes are more bioactive than free ligand and can be excellent candidates for further evaluations in the biological area.